POINTS AND LINES IN PROJECTIVE SPACE: A MODERN APPROACH - Burxonova Muslima Nazirjon qizi; Dilnoza Xaytmirzayevna Maxmudova (International Scientific and Current Research Conferences, 2025)
This paper investigates the modern understanding of points and lines in projective space, emphasizing algebraic and geometric properties. We explore homogeneous coordinates, the incidence relations between points and lines, and their applications in modern geometry and computer vision. Diagrams and algebraic formulations enhance clarity and application potential.